Cost-Utility Analysis of Once-Weekly Semaglutide, Dulaglutide, and Exenatide for Type 2 Diabetes Patients Receiving Metformin-Based Background Therapy in China - Hu, Shanshan; Wang, Shuowen; Qi, Chendong; Gu, Shengying; Shi, Chenyang; Mao, Lin; Fan, Guorong (Frontiers in Pharmacology, 2022)
Introduction: The substantial financial burden associated with type 2 diabetes (T2D) over a lifetime cannot be neglected. Therefore, the objective of this study was to evaluate the pharmacoeconomic value of three once-weekly GLP-1 RAs, namely subcutaneous semaglutide (sc. SEMA), dulaglutide (DULA), and extended-release exenatide (e-r EXEN), in treating patients with T2D that cannot be controlled with metformin-based background therapy, and to find a suitable price reduction for non-cost-effective medications, to provide reasonable recommendations to the administration for adjusting drug prices. Methods: The baseline characteristics of the simulation patient cohort were sourced from a comprehensive meta-analysis synthesizing 453 trials evaluating 21 hypoglycemic agents from nine categories of drugs. The UKPDS OM2 was applied to project the long-term effectiveness and costs from a Chinese health care provider’s perspective. After cost-utility analysis, the reasonable price adjustment of non-cost-effective options was explored via binary search. Uncertainty was measured by means of sensitivity analysis. Results: After a 40-year simulation, the sc. SEMA, DULA, and e-r EXEN groups yielded 9.6315, 9.5968, and 9.5895 quality-adjusted life years (QALYs), respectively. In terms of expenditure, the total costs for the sc. SEMA, DULA, and e-r EXEN groups were 42012.47, 24931.27, and 40264.80, respectively. DULA was dominant over e-r EXEN due to the higher QALYs and lower total costs. The ICURs of sc. SEMA vs. DULA and sc. SEMA vs. e-r EXEN were 492994.72/QALY and 41622.69/QALY (ICUR > λ), respectively, indicating that sc. SEMA was not more cost-effective than DULA or e-r EXEN. The INMB and absolute NMB yielded the same conclusions which were robust to one-way, scenario, and probabilistic sensitivity analyses. After several assumptions in the binary search, sc. SEMA and e-r EXEN appear to become cost-effective when their annual costs are decreased by 57.67% and 70.34%, respectively, with DULA as a counterpart. Conclusion: From the cost-utility analysis, DULA appears to be the most cost-effective option among sc. SEMA, DULA, and e-r EXEN for the treatment of patients with T2D receiving metformin-based background therapy. With a 57.67% or 70.34% reduction in cost, sc. SEMA or e-r EXEN, respectively, would become as cost-effective as DULA in China.